PRILAKU PASIEN HIPERTENSI DI UPT PUSKESMAS MEDAN SUNGGAL: PRILAKU PASIEN HIPERTENSI - Ilham Syahputra Siregar; Irma Handayani; Leny Suarni (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2026)
Hypertension is a non-communicable disease and one of the leading causes of morbidity and mortality worldwide. Individuals with a family history of hypertension have a twofold greater risk of developing hypertension compared to those without such a history. The prevalence of hypertension increases with age, and men tend to develop hypertension earlier than women. Successful hypertension control is influenced by patients’ behavior in adhering to treatment, maintaining a healthy diet, engaging in physical activity, and attending regular health check-ups. This study used a descriptive research design with a purposive sampling technique. The research was conducted at Puskesmas Medan Sunggal from March to August 2025. The population consisted of 250 individuals, with a sample of 38 respondents. The results showed that hypertension was more common among women, accounting for 60.52% of respondents. The majority of respondents were aged 50–59 years (50%). Most respondents were employed (65.79%) and had a senior high school/vocational high school education (60.32%). Regarding knowledge about hypertension, most respondents had a good level of knowledge (57.9%). Positive attitudes toward hypertension were found in 71.05% of respondents, while good preventive and management behaviors were demonstrated by 73.68% of respondents. This study is expected to provide useful information for future researchers regarding hypertension. Health workers are also encouraged to further improve education and awareness programs related to the dangers of hypertension.